2008
DOI: 10.1063/1.2884527
|View full text |Cite
|
Sign up to set email alerts
|

Direct structural evidences of Mn11Ge8 and Mn5Ge2 clusters in Ge0.96Mn0.04 thin films

Abstract: Effect of growth temperature on morphology, structure and luminescence of Eu-doped GaN thin films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
61
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 21 publications
4
61
1
Order By: Relevance
“…The similar self-assembled nanostructures were also observed by other groups in Mn-doped Ge thin films prepared by molecular beam epitaxy ͑MBE͒. 8,12 On the other hand, randomly distributed coherent GeMn nanodots with a nonuniform size have been grown on Ge substrates using MBE; 7 however, no spontaneous magnetization was observed at all temperatures ͑down to 2 K͒. This indicates that different morphologies ͑nanocolumns/nanodots͒ of the GeMn clusters may result in different magnetic properties.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…The similar self-assembled nanostructures were also observed by other groups in Mn-doped Ge thin films prepared by molecular beam epitaxy ͑MBE͒. 8,12 On the other hand, randomly distributed coherent GeMn nanodots with a nonuniform size have been grown on Ge substrates using MBE; 7 however, no spontaneous magnetization was observed at all temperatures ͑down to 2 K͒. This indicates that different morphologies ͑nanocolumns/nanodots͒ of the GeMn clusters may result in different magnetic properties.…”
mentioning
confidence: 52%
“…1 For this reason, Ge-based ͑such as GeMn͒ diluted magnetic semiconductors ͑DMSs͒, compatible with the current Si technology, have been studied extensively. [2][3][4][5][6][7][8][9][10][11][12][13] It is well understood that the low solubility of Mn in Ge has been a main barrier to achieve a high T c DMS GeMn film with high Mn concentration and uniformly distributed Mn in Ge. As a consequence, Mn-rich precipitates, such as Mn 5 Ge 3 , 9,14,15 Mn 5 Ge 2 , and Mn 11 Ge 8 , 12 are usually observed and are believed to be responsible for the observed ferromagnetism up to room temperature.…”
mentioning
confidence: 99%
“…These defects are located exactly over the islands with a vertical boundary for stopping the planar defects, indicating that the formation of the defects is closely related to the buried islands. Figure 3͑a͒ is a selected area electron diffraction pattern taken along a ͗110͘ zone axis of the Si capping layer with defects and exhibits the diffraction spots of a diamond structure together with additional weaker spots ͑appearing at onethird of ͕111͖ diamond diffraction spots͒, which were also observed in other diamond 11 or zinc blende 12 structured materials. These weak diffraction spots correspond to a triplet periodicity in the stacking sequence along the ͕111͖ plane.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] One of the key issues to achieve GeMn DMS is to uniformly dope Mn into the Ge matrix. 7,10 It has been reported that the Mn dilution in Ge depends strongly upon the substrate temperature and that inhomogeneous Mn distributed in the Ge films tends to the formation of Mn-rich precipitates, such as Mn 5 Ge 3 4-6 and Mn 11 Ge 8 8,9 phases, which makes it complicated to understand the origin of ferromagnetism of GeMn DMS films. Most of the previous studies have been focused on the structural and magnetic properties of these Mn-rich clusters in GeMn films grown on Ge substrates.…”
mentioning
confidence: 99%